A Product-Driven System Approach for Multilevel Decisions in Manufacturing Planning and Control - Parada-Daza, V (Taylor and Francis Ltd., 2014)
Decision-making in Manufacturing Planning and Control Systems uses processes that consider several levels of product aggregation and different time horizons. Decisions rendered on each level do not always have similar goals. The problem is that building Intelligent Manufacturing Systems (IMS) involves coordinate decisions on different levels to achieve a common objective. There is no current research on IMS regarding coordination among decision levels in Product-driven Control Systems, hence simulations of the planning and control processes should be conducted to analyze the behavior of multilevel objectives. Accordingly, in this paper a simulation model gives account of different coordination issues between tactical and operational levels. At the tactical level, production plans are generated by an Advanced Planning and Scheduling system, whereas at the operational level, a distributed decision rule is used. The whole simulation makes decentralized decisions that are managed by production lots represented by holons. Results for our simulation indicate that coordination among active lots is capable of making effective multilevel distributed decisions when compared with conventional approaches. © 2014 The Author(s). Published by Taylor & Francis.